(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2011)
This article deals with the analysis of professional competence, its nature and structure based on position trainingof future economists. On the basis of the scientific literature, specific such basic concepts: competence, competence,professional competence economist components of professional competence in economics.